Health care disruption inequalities during Covid-19: Evidence from eleven longitudinal studies. (20th October 2021) - Parsons, S; Maddock, J; Di Gessa, G; Green, MJ; Thompson, EJ; Stevenson, AJ; Kwong, ASF; McElroy, E; Silverwood, RJ; Katikireddi, SV
Abstract: Like other health systems worldwide, the UK, the National Health Service (NHS) has faced major disruptions due to high Covid-19 burden and repeated lockdown measures. These disruptions can have both short and long-term health impacts. The NHS provides free healthcare and prioritises equity of delivery, but despite this, inequalities in access to health care remain and it is plausible that pandemic-related disruptions affect different groups disproportionally, thus widening health inequalities. This paper investigates associations between well-established axes of health inequality (sex, age, social class, education and ethnicity) and self-reported health care disruptions (medication access, procedures, or appointments) in over 65, 000 participants across eleven longitudinal studies in the UK. Participants reported disruptions from March 2020 through to as late as January 2021. We obtained study-specific estimates using logistic regression models and combined them in a random-effects meta-analysis. Analyses were adjusted for sex, age and ethnicity where relevant. Between 10.1% (Millennium Cohort Study) and 31.8 % (Understanding Society) of study participants reported experiencing health care disruptions. Results show that females (OR: 1.27 [95%CI: 1.15, 1.4]; I2=56%), older participants (e.g. OR: 1.39 [1.13, 1.72]; I2=77% for 65-75y vs 45-54y), and non-white ethnic minorities (OR: 1.17 [1.02, 1.34]; I2=0% vs white) were more likely to report healthcare disruptions. Those in a more disadvantaged social class (e.g. OR: 1.18 [1.08, 1.21]; I2=0% for manual/routine vs managerial/professional) were also more likely to report healthcare disruptions, but no clear differences were observed for education. Our findings highlight inequities in healthcare disruptions, which, if unaddressed, could contribute to the maintenance or widening of existing health inequalities.